Fostering equitable access to employability development through an institution-wide, in-curricular strategy - Bennett, Dawn (Palgrave Macmillan, 2021)
Inequitable access to employability development opportunities presents a risk to equitable retention, student success and graduate outcomes among students with disadvantage. With a focus on equity, this chapter describes the development and initial incorporation of a strength-based, in-curricular and whole-of-institution approach to employability. At the core of the initiative was the metacognitive framing of employability as the ability to find, create and sustain meaningful work across the career lifespan and in multiple settings. The chapter outlines the challenges and opportunities inherent in a whole-of-institution approach. Key stakeholders including students, academic staff, career practitioners and institutional leaders are discussed. The chapter includes a synthesis of what was learned and makes recommendations for the design of similar equitable approaches.